TRAINING ON STANDARD OPERATING PROCEDURES (SOP) AND SERVICE EXCELLENCE FOR THE FOOD AND BEVERAGE DEPARTMENT AT THE BENCONGAN INDAH RESTAURANT MSME - Jessica Mary Lauw; Amelda Pramezwary; Julita Then (IJOSPOL - International Journal of Social, Policy and Law, 2026)
The culinary micro, small, and medium enterprise (MSME) sector in Indonesia faces significant challenges in maintaining service consistency due to the absence of structured Standard Operating Procedures (SOP). This Community Service (PkM) program aimed to improve the knowledge and practical skills of the management and service staff at Bencongan Indah Restaurant in implementing Food And Beverage Service SOPs and Serivce Excellence standards aligned with the professional hospitality industry. The program was conducted on May 25, 2026, at Bencongan Indah Village Office, involving 26 participants comprising restaurant managers and waitstaff. Implementing consisted of four stages preparation and coordination, program socialization, interactive core training, and evaluation with reporting. Training materials covered the guest service cycle, taking order techniques and suggestive selling, handling complaint using the HEAT method (Hear, Empathize, Apologize, Take Action), and personal hygiene and grooming standards. Evalution was carried out through pre-test and post-test instruments quantitatively. Results demonstrated an average knowledge improvement form 80.4% to 95.8%, reflecting a 15.4% increase. The highest gains were recorded in post-transaction service etiquette (23.1%) and customer handling complaint (19.2%). This PkM activity effectively bridged the gap between academic theory and the practical operational needs of culinary MSMEs. As a follow-up, periodic evalution visits and program expansion to additional MSME partners in the Bencongan Indah area are recommended to promote sustainanble improvement in local culinary competitiveness.